Зулали - Абгарян Наринэ Юрьевна (Эксклюзивная новая классика, 2021)
Экземпляры: Камская библиотека (20211124) / Инвентарный номер: 11766 / Цена: / Сис.шифр: 84(2Рос=411.2)6 / Авт.знак: А 13 / ГРНТИ: 17.82.30 / ББК: 84(2Рос=411.2)6